Financial portfolio performance of Belgian households: A nonparametric assessment - Laurens Cherchye; Bram de Rock; Dieter Saelens (National Bank of Belgium, 2024)
We analyze the financial portfolio performance of Belgian households, using data from the 2010, 2014 and 2017 waves of the Household Finance and Consumption Survey survey. We document the characteristics of households that participate in risky asset markets, and we examine which households achieve good financial portfolio performance. To this end, we propose a nonparametric method for performance measurement that naturally integrates the well-known Sharpe ratio. The method produces an intuitive "efficiency" measure that quantifies the evaluated household's portfolio performance relative to the observed performance of other (best performing) households. It allows us to account for cross-household variation in risk-free return rates and to mitigate the impact of outlier behavior. We report significant cross-sectional variation in portfolio efficiency. High educated, non-retired and wealthier households generally achieve higher levels of efficiency, as do households with a female head. These findings can be instrumental in developing specifically tailored financial education programs and may have implications for the evolution of (long-term) wealth inequality. Lastly, we report that households improve their performance over time, suggesting a learning-by-doing effect.
Keywords: D14; G11; G50; 330; household finance; benchmarking; mean-variance portfolios; Sharpe ratio; nonparametric method; Belgian households